INTERACTION OF MOLYBDENUM (VI) WITH TARTARIC ACID WATER LIQUID (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
Interaction of molybdenum(VI) with tartaric acid at certain concentration of perchloric acid (1 M) is studied using spectrophotometric methods (isomolecular series, shifts of equilibrium, Asmus straight line-and ion-exchange chromatography). It is established that at the indicated interaction there appears a complex 1 : 1 M  ratio. The  contents of the formed complex and the value of the resistance constant are defined.
Keywords: molybdenum(VI); tartaric acid; resistance constant; spectrophotometric methods